IS LEARNING ENGLISH BORING WITH GAMIFICATION? - Muhamad Laudy Armanda; Lilia Indriani (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2022)
COVID-19 is a global pandemic that has brought significant disruptions to education. EFL educators ought to be aware of suitable methods during hybrid learning. The Digital learning trend that is reshaping EdTech for Gen-Z is gamification. It is the application of game-design elements and game principles in non-game contexts. Thus, this study aims to shed light on student teachers' perceptions on gamification for boostering motivation in hybrid language classes. To assess the perception, we tracked it of 32 students. Critical aspects highlighted by students in their learning experience were also analyzed. Evidences show the usefulness of gamification in improving students’ motivation and, to some extent, in changing their habits.